1989
DOI: 10.1073/pnas.86.22.8972
|View full text |Cite
|
Sign up to set email alerts
|

Degranulation of human mast cells induces an endothelial antigen central to leukocyte adhesion.

Abstract: To understand better the role of mast cell secretory products in the genesis of inflammation, a system was developed for in vitro degranulation of human mast cells in skin organ cultures. Within 2 hr after morphine sulfate-induced degranulation, endothelial cells lining microvessels adjacent to affected mast cells expressed an activation antigen important for endothelial-leukocyte adhesion. Identical results were obtained when other mast cell secretagogues (anti-IgE, compound 48/80, and calcium ionophore A2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(115 citation statements)
references
References 32 publications
6
109
0
Order By: Relevance
“…The reasons underlying these differences in reported responses to MIF treatment are unclear, although it is conceivable that they stem from functional differences in endothelial cells from different vascular sites. In vivo studies have established that endothelial cells from arterial and venous sources have differing capacities in terms of adhesion molecule expression (49)(50)(51)(52). Studies in which MIF treatment was found to induce mononuclear leukocyte arrest were performed using aortic endothelial cells, whereas the present studies used endothelial cells derived from umbilical veins (26).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons underlying these differences in reported responses to MIF treatment are unclear, although it is conceivable that they stem from functional differences in endothelial cells from different vascular sites. In vivo studies have established that endothelial cells from arterial and venous sources have differing capacities in terms of adhesion molecule expression (49)(50)(51)(52). Studies in which MIF treatment was found to induce mononuclear leukocyte arrest were performed using aortic endothelial cells, whereas the present studies used endothelial cells derived from umbilical veins (26).…”
Section: Discussionmentioning
confidence: 99%
“…anti-lgE or compound 48/SO. and correlated with ma.st ceil degranulation [10,14]. ELAM-I expression appears to be TNF-dependent and can be inhibited by prior incubation wilh cromolyn.…”
Section: Discussionmentioning
confidence: 93%
“…ELAM-I expression appears to be TNF-dependent and can be inhibited by prior incubation wilh cromolyn. a drug able to prevent mast cell degranulation [10]. In a recent report, Walsh f/«/, demonstrated thai mast cells were the main source of TNF in normal human dermis, and that iheir degranulation released TNF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 stimulates the polarization of naive T cells (Th0 cells) to Th2 cells via induction of IL-4 gene expression (Rincon et al, 1997) and in uences IgE synthesis (Vercelli et al, 1989). TNF-a stimulates B lymphocyte activity (Kehrl et al, 1987) and is increased in the lungs of asthmatics (Casale et al, 1996), where it facilitates extravasation of leukocytes into the tissue via upregulation of vascular cell adhesion molecule 1 (VCAM-1) (Klein et al, 1989;Moser et al, 1992). In addition to the activation processes just described, pulmonary in ammation also features edema from epithelial damage, which may result in a loss of barrier function and enhanced translocation of inhaled antigen to the submucosa (Matsamura, 1970).…”
Section: Resultsmentioning
confidence: 99%